Effect of tramadol on extubation response and quality of emergence following Supratentorial surgery: a randomised controlled trial - Asma Abdus Salam; Rehman, Azhar; Shamim, Muhammad Shahzad; Khan, Fauzia Anis (Journal of the Pakistan Medical Association, 2022)
Objectives: To observe the effect of a single dose of tramadol 1mg/kg on haemodynamic changes related to extubation, and to assess the quality of emergence as judged by incidence of cough, laryngospasm and bronchospasm. Method: The double-blind randomised controlled trial was conducted at the Department of Anaesthesiology, Aga Khan University Hospital, Karachi, from 2016 to 2017, and comprised patients of either gender aged 18-65 years scheduled for elective supratentorial craniotomy under general anaesthesia. The patients were randomised to two Tramadol and Saline groups. The drug was given 45 minutes before extubation at the time of dura closure. The patients were extubated after resumption of adequate spontaneous breathing. Invasive blood pressure and heart rate were recorded one minute before reversal, at 1 minute interval for five minutes and then every 10 minute for 30 minutes after extubation. Cough, laryngospasm and bronchospasm were noted. Pain, post-operative nausea, vomiting, convulsions and conscious levels were also noted till 6 hours post-operatively. Data was analysed using SPSS 19. Results: Of the 80 patients enrolled, 79(98.75%) completed the study. Of them, 38(48%) were in the Tramadol group; 27(71.1%) males and 11(28.9%) females with a mean age of 43.42+/-13.2 years. The remaining 41(52%) patients were in the Saline group; 28(68.3%) males and 13(31.7%) females with a mean age of 45.9+/-15.9 years. Intergroup comparison showed no significant difference in the extubation response (p>0.05), but the changes in blood pressure and heart rate were shorter in magnitude and duration in the Tramadol group compared to the baseline. Significant rise in blood pressure and heart rate was observed in the Saline group at 5 minutes after extubation (p=0.046). There was no difference in the quality of emergence as judged by cough or secondary complications (p>0.05). Conclusion: Tramadol 1mg/kg was considered superior in attenuating the duration and magnitude of haemodynamic response in the shape of hypertension and tachycardia during extubation, but did not affect other parameters in patients undergoing craniotomy. Clinical Trial Number: Clinical Trials.gov PRS: NCT02964416 https://clinicaltrials.gov/ct2/show/NCT02964416 Key Words: Craniotomy, Endotracheal extubation, Haemodynamics, Opioid, Cough.